Patients Screening Positive for Body Dysmorphic Disorder Show No Significant Health-Related Quality of Life Gain after Functional Septorhinoplasty at a Tertiary Referral Center - Bulut, Olcay C.; Wallner, Frank; Oladokun, Dare; Plinkert, Peter K.; Baumann, Ingo; Hohenberger, Ralph (Facial Plastic Surgery, 2018)
Body dysmorphic disorder (BDD) is a psychiatric disorder defined by an excessive concern about one's physical appearance, especially regarding slight or imagined abnormities of the body. This study was conducted to compare postoperative quality of life (QOL) changes after primary septorhinoplasty among patients screening positive and those screening negative for BDD. Two common instruments for the screening of BDD were used namely the Dysmorphic Concern Questionnaire (DCQ) and the BDD Concern Questionnaire (BDDQ). For the determination of QOL changes, three validated screening instruments were used. The Functional Rhinoplasty Outcome Inventory (FROI-17) and the Rhinoplasty Outcomes Evaluation (ROE) were used as disease-specific instruments and the Short Form 36 Health Survey (SF-36) was used as a general instrument. All patients completed the FROI-17, the ROE, and the SF-36 preoperatively and 60 months postoperatively. The BDD questionnaires were singularly obtained 60 months after surgery. The authors identified 9.8% of our patients with a possible BDD diagnosis. The patients screening positive for BDD showed significantly lower ROE scores postoperatively, compared with those screening negative for BDD. QOL gains detected by the disease-specific instruments (ROE and FROI-17) were only significant in the non-BDD group. No significant QOL gains were detectable with the FROI-17, the ROE, and the SF-36 in the BDD group. In patients screening negative for BDD, QOL, as measured with the SF-36, improved significantly in five categories: physical functioning, role-functioning physical, bodily pain, general health, and social functioning. Patients screening positive for BDD did not improve in any categories of the general SF-36 questionnaire. Instead, their score in the “mental health” category was significantly lower 5 years after their surgery compared with preoperatively. Patients retrospectively screening positive for BDD in our cohort did not improve in QOL postoperatively. Alternative nonsurgical treatments such as cognitive behavioral treatment and/or selective serotonin reuptake inhibitors have been reported to be effective and should be considered as the treatment of choice. Some studies suggest that a smaller subgroup of BDD patients may benefit from functional rhinoplasty. Further research and larger long-term prospective outcome studies are needed to understand the influence of BDD symptoms on postoperative satisfaction and QOL changes after septorhinoplasty.
Keywords: body dysmorphic disorder; rhinoplasty; quality of life; BDD; FROI-17; ROE